Dyslexia, literacy and inclusion : child-centred perspectives - MacBlain, Sean.; Louise Long;Jill Dunn (India : Sage Publications Limited, 2015)
With case study examples that cover early years and primary, this book takes a child-centred approach by putting the focus on emotional well-being, offering individual strategies for raising literacy standards among children with dyslexia.
Part1. New Horizons for Pupils with Dyslexia -- Part2. Building Capacity to Raise Literacy Standards for Children with Dyslexia and Developmental Literacy Difficulties -- Part3. Literacy in Contemporary Settings -- Part4. Conclusion .
Includes index.
Keywords: DYSLECIC CHILDREN EDUCATION